2017
DOI: 10.1111/opec.12094
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption, human capital investment and economic growth in South Africa: a vector error correction model analysis

Abstract: This paper investigates the dynamic causal relationship between energy consumption, human capital investment and economic growth in South Africa for the period 1960–2015 within the vector error correction model (VECM) framework. It was revealed that there is cointegration among the variables. The causality test result reveals that there exists a long‐run bi‐directional relationship between economic growth and energy consumption. While on the other hand, a long‐run unidirectional causal relationship was discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…For South Africa, a similar study is conducted by Ilesanmi and Tewari (2017). The study investigates the dynamic causal relationship between energy consumption, human capital investment and economic growth for the period 1960-2015 employing VECM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For South Africa, a similar study is conducted by Ilesanmi and Tewari (2017). The study investigates the dynamic causal relationship between energy consumption, human capital investment and economic growth for the period 1960-2015 employing VECM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the evidence on the investment in human capital and energy consumption is inconclusive and is lacking to shed much light on any reductions in resulting emissions (for instance, contrast Diks and Wolski2015,Ilesanmi and Tiwari 2017, Fang andWolski 2017).…”
mentioning
confidence: 99%
“…First, a DR program is very likely to be successful where economic growth rates are higher. Studies have shown that infrastructure investmentincluding investment in energy infrastructureleads to higher economic growth and, in some cases, that growth spurs investment [53][54] [55]. It is thus possible that DR programs are more likely to be implemented, and consequently more likely to be successful, in regions with higher growth rates.…”
Section: Discussionmentioning
confidence: 99%